Perencanaan Operasional Live Streaming Agency di PT Check Out Time (COT) - Devy Andriany; Edi Hamdi; Dimas Angga Negoro; Muhammad Dhafi Iskandar (Yayasan Literasi Sains Indonesia, 2025)
This study aims to develop PT COT's operational planning to address the dynamics of the e-commerce live streaming industry. The research method used is descriptive qualitative with a case study approach, through interviews, observations, and documentation studies. The results show that PT COT's operational planning includes five main components: business establishment stages, operational goals and objectives, operational design, operational delivery, and cost projections. The operational strategy focuses on fulfilling business legality, providing studio facilities, utilizing BICOT (Business Intelligence for COT) technology, and developing an integrated supply chain model based on an orchestrator. PT COT's short-, medium-, and long-term goals demonstrate a strategic and sustainable development direction. In the short term, the main focus is directed at increasing studio capacity to increase productivity and expand existing service capabilities. In the medium term, the company plans to open a new branch in Surabaya as a geographic expansion measure to strengthen its market position and reach more customers. Meanwhile, in the long term, the strategy focuses on service diversification and the formation of a brand ambassador agency that can expand the business portfolio and create added value through collaboration with various brands.